Exploring the psychological impact of long COVID: symptoms, mechanisms, and treatments - Shen, Shi; Zhao, Xin; Pei, Jianxin; Wang, Bijue; Hou, Jingjing; Chai, Ru; Guo, Yiqiong; Li, Feiyu; Hao, Jian; Wu, Zhonglan (Frontiers in Psychiatry, 2025)
Long COVID (LC) refers to a multisystem condition that persists after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for coronavirus disease 2019 (COVID-19). In addition to physical symptoms, the psychological impact is particularly pronounced. This review summarizes the manifestations, potential mechanisms, epidemiological characteristics, and current interventions related to psychological disorders in LC. Drawing on domestic and international literature, it highlights anxiety, depression, cognitive dysfunction, and post-traumatic stress disorder (PTSD) as the primary psychological symptoms. These symptoms may be associated with neuroinflammation, immune abnormalities, vascular dysfunction, and psychosocial stress. Although research in this area is still developing, psychotherapy, pharmacotherapy, neuromodulation, and lifestyle interventions show promise as treatment approaches. This review aims to provide insights that can inform future research on clinical treatments and psychological care for individuals with LC.